Electrical Activity in a Time-Delay Four-Variable Neuron Model under Electromagnetic Induction - Tang, Keming; Wang, Zuolei; Shi, Xuerong (Frontiers in Computational Neuroscience, 2017)
To investigate the effect of electromagnetic induction on the electrical activity of neuron, the variable for magnetic ﬂow is used to improve Hindmarsh-Rose neuron model. Simultaneously, due to the existence of time-delay when signals are propagated between neurons or even in one neuron, it is important to study the role of time-delay in regulating the electrical activity of the neuron. For this end, a four-variable neuron model is proposed to investigate the effects of electromagnetic induction and time-delay. Simulation results suggest that the proposed neuron model can show multiple modes of electrical activity, which is dependent on the time-delay and external forcing current. It means that suitable discharge mode can be obtained by selecting the time-delay or external forcing current, which could be helpful for further investigation of electromagnetic radiation on biological neuronal system.